Characterization of Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae From Retail Food in China - Ye, Qinghua; Wu, Qingping; Zhang, Shuhong; Zhang, Jumei; Yang, Guangzhu; Wang, Juan; Xue, Liang; Chen, Moutong (Frontiers in Microbiology, 2018)
In this study, we characterized the β-lactamase genes of cephalosporin-resistant Enterobacteriaceae isolated from retail foods in China. Of 1024 Enterobacteriaceae isolates recovered from raw meat products, aquatic products, raw vegetables, retail-level ready-to-eat (RTE) foods, frozen foods, and mushrooms from 2011 to 2014, 164 (16.0%) showed cefotaxime (CTX) and/or ceftazidime (CAZ) cephalosporin resistance, and 96 (9.4%) showed the extended-spectrum β-lactamase (ESBL) phenotype. More than 30% isolates were resistant to all antimicrobial agents except carbapenems (MEM 3.1% and IPM 5.2%), cefoxitin (FOX 6.3%), and amoxicillin/clavulanic acid (AMC 26%), and 94.8% of the strains were resistant to up to seven antibiotics. Polymerase chain reaction analysis showed that blaTEM (81.9%) was the most common gene, followed by blaCTX-M (68.1%) and blaSHV (38.9%). Moreover, 16.8% (72/429) of food samples contained ESBL-positive Enterobacteriaceae, with the following patterns: 32.9% (23/70) in frozen foods, 27.2% (5/29) in mushrooms, 17.6% (24/131) in raw meats, 13.3% (4/30) in fresh vegetables, 11.1% (8/72) in RTE foods, and 9.3% (9/97) in aquatic products. Conjugation experiments demonstrated that the 22 of 72 isolates were transconjugants that had received the β-lactamase gene and were resistant to β-lactam antibiotics as well as some non-β-lactam antibiotics. These findings demonstrated that retail foods may be reservoirs for the dissemination of β-lactam antibiotics and that resistance genes could be transmitted to humans through the food chain.